Monitoring Iran's Health System in the Perspective of Global Health Reports - Kambiz Abachizadeh; Reza Shekarriz-Foumani; Maryam Mohseny; Narges Malih; Akbar Shafiee; Ayad Bahadori-Monfared (Shahid Beheshti University of Medical Sciences, 2020)
Background and Objective: Global health reports are valuable sources in all health areas for policymakers. The aim of our study was to review the global reports published within ten years, focusing on the situation and functions of Iran health system. Materials and Methods: The study reviewed global health reports. In our study and with a systematic approach, we attempted to find and review all the main published reports from 2008 to 2018, using appropriate search strategies. At first, we assessed how these reports are published and who are the main participants. Then, the importance of the area and approach of the report was assessed. The indicators at international and national levels from the aspect of both the process and outcomes were the fundamental part of our analysis. Finally, special experiences from Iran were extracted from each global report. Results: Sixteen global reports in the areas of non-communicable disease, communicable diseases, mental health, and injuries were selected and indicators related to the world and Iran was extracted. Conclusion: Assessment of the global reports demonstrated that the situation of Iran's health system in the areas of controlling the non-communicable diseases, maternal health, and water safety was favorable. However, the situation in the areas of unintentional injuries and happiness was unfavorable. The situation in the field of mental health and violence prevention was intermediate. Ethical code: IR.TUMS.NIHR.REC.1396.50 DOI: http://doi.org/10.26675/ch.v7i4.26675.